VIABILITAS PUPUK HAYATI PENAMBAT NITROGEN (Azotobacter dan Azospirillum ) EKOSISTEM PADI SAWAH PADA BERBAGAI FORMULASI BAHAN PEMBAWA - Danapriatna, Nana; Simarmata, Tualar (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
Generally microbes in biofertilizer packaged in a carrier material powder and liquid form. Each inoculant requires media requirements and characteristics of differentcarrier materials. This research aims to study the composition of the carrier material N2 fixation biofertilizer (Azotobacter and Azospirillum) from paddy ecosystem in the form of powder. The study was conducted in two stages: (a) Test Viability of biofertilizer compositions from three carriers which performed at the Laboratory with the observed response variable bacterial populations on a regular basis ie 1, 2, 6, 10, 14, 18, 30 and, 42 weeks after production and (b) Testing the addition of nutrients and the ratio of pure cultures with the carrier materials on viability of bacteria using a complete randomized block design consisting of 12 treatment combinations of nutrients and the addition of pure cultures with different ratios of carrier. The experimental results show that the carrier material of peat and compost is the best carrier with the highest bacterial viability until the age of 42 weeks after the production of fertilizer. The formulation of biofertilizer with addition of 0.5% nutrient + 35% culture and biofertilizer formulation with the addition of 1% nutrient + 30% culture better in supporting the viability of the bacteria until the age of 20 weeks after production.